Mechanical comparison of two internal rigid fixation systems used for fixing facial fractures (an in vitro study) - Zuluaga-Londoño, Juliana; Giraldo-Niño, José Fernando; Garzón-Rayo, Herney (Revista Facultad de Odontología Universidad de Antioquia, 2016)
Introduction: currently, talking about highly resistant aesthetic dental restorations implies talking of yttrium-stabilized zirconium dioxide (Y-TZP) ceramic systems, which have become important due to their good mechanical and physical properties and high biocompatibility. One of the main complications of such restorations nowadays is ceramic coating delamination. It has been shown that the interface of both materials is the origin of failure because of poor bonding strength, mainly due to excessive internal tension in the coating material caused by a difference in the thermal expansion coefficients of both materials. Methods: 15 zirconium blocks were randomly sorted out into 3 groups: one control group and two groups were the surface of bonding to the ceramic coating was modified by grinding with rounded diagonal and squared burs respectively. Once the samples were sintered, the ceramic coating was applied and shear bond strength tests were performed. A one-way analysis of variance (ANOVA) was conducted. The Tukey’s range test was used to compare the difference in results among groups. Results: the results in this study were very heterogeneous. The average shear bond strength values were 20.2 MPa ± 6.8 MPa for Group A; 5.87 MPa ± 4.87 Mpa for Group B, and 3.69 ± 2.68 MPa for Group C. Conclusions: it is not necessary to prepare the zirconium surface with mechanical grinding in order to improve shear bond strength in ceramic coatings.